First record of cinnamon coloration in opossum Didelphis sp. in México - Tenorio-Rodríguez, Paola A.; Cab-Sulub, Leticia; Moreno-Figueroa, Luis Daniel (Therya Notes, 2024)
Pigmentation plays a vital role in vertebrate coloration, influenced by genetic and environmental factors. Albinism, leucism, melanism, and flavism are notable color anomalies in vertebrates. This manuscript documents the first record of flavism in Didelphis sp. in México, captured in Yucatán Península. In July 2023, 2 orphaned young male opossums were rescued from a backyard in an urbanized area in Chuburná Hidalgo, in Yucatán, México, and transported to a rehabilitation shelter in Mérida. One, displayed a typical dark fur, while the other showed a cinnamon coloration. Following hand-rearing, the opossums were released into the wild after reaching appropriate size and weight. Individual cinnamon maintained the coloration and exhibited an orange-brown pelage, distinguishing him from the other one. The cinnamon pigmentation in the opossum is likely not only the result of a genetic mutation affecting melanin metabolism but also influenced by other evolutionary pressures in this region. Anomalous coloration in vertebrates can be linked to genetic diversity, habitat quality, or environmental contamination. Additionally, population isolation due to habitat fragmentation could play a significant role. Comprehensive genetic and population studies are needed to fully understand the impact of these factors on the population. Despite risks, opossums' adaptability may ensure survival, as seen in similar cases.